Mediation analysis of aortic stiffness and renal microvascular function - Woodard, Todd; Sigurdsson, Sigurdur; Gotal, John D; Torjesen, Alyssa A; Inker, Lesley A; Aspelund, Thor; Eiriksdottir, Gudny; Gudnason, Vilmundur; Harris, Tamara B; Launer, Lenore J; Levey, Andrew S; Mitchell, Gary F (Journal of the American Society of Nephrology, 2015)
Aortic stiffening, assessed by carotid-femoral pulse wave velocity, is associated with CKD. Transmission of excessive flow pulsatility into the low-impedance renal microvasculature may mediate this association. However, direct analyses of macrovascular-microvascular relations in the kidney are limited. Using arterial tonometry, iohexol clearance, and magnetic resonance imaging, we related arterial stiffness, GFR, urinary albumin excretion, and potential mediators, including renal artery pulsatility index, renal vascular resistance, and arterial volume in the cortex, in 367 older adults (ages 72-92 years) participating in the Age, Gene/Environment Susceptibility-Reykjavik Study. In a model adjusted for age, sex, heart rate, and body size, aortic stiffness was related to GFR (Slope of regression B=-2.28±0.85 ml/min per SD, P=0.008) but not urine albumin (P=0.09). After accounting for pulsatility index, the relation between aortic stiffness and GFR was no longer significant (P=0.10). Mediation analysis showed that 34% of the relation between aortic stiffness and GFR was mediated by pulsatility index (95% confidence interval of indirect effect, -1.35 to -0.29). An additional 20% or 36% of the relation was mediated by lower arterial volume in the cortex or higher renal vascular resistance, respectively, when offered as mediators downstream from higher pulsatility index (95% confidence interval of indirect effect including arterial volume in the cortex, -2.22 to -0.40; 95% confidence interval of indirect effect including renal vascular resistance, -2.51 to -0.76). These analyses provide the first evidence that aortic stiffness may contribute to lower GFR by transferring excessive flow pulsatility into the susceptible renal microvasculature, leading to dynamic constriction or vessel loss.